We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
422
1
avatar

1. Find the center of the circle with equation $9x^2-18x+9y^2+36y+44=0$

2.The graph of $y=ax^2+bx+c$ is given below, where $a$, $b$, and $c$ are integers. Find $a$. 

 Feb 21, 2018

Best Answer 

 #1
avatar+18057 
+2

1. 9x^2-18x      +9y^2 + 36y      = -44    divide thru by 9

      x^2 - 2x        + y^2 +4          = -44/9    'complete the square' for x and y

    ( x-1)^2          + (y+2)^2         = -44/9  + 1 + 4

     (x-1)^2 + (y+2)^2   =   1/9      Now this is standard form for a circle (x-h)^2 + (y-k)^2 = r^2 

where center is h,k  and r = radius   

center =  1,-2    radius = 1/3

 

2. Let's set this up as vetex form for a parabola     h, k = vertex = 1,3  (from graph)

   so      a(x-1)^2  + 3 =y   is the equation for this parabola...now let's find 'a'

           a convineint point which must satisfy this equation (on the graph) is  0,1 ...substitute this

 

          a (0-1)^2 + 3 = 1

              a+3 = 1

               a= -2      so the equation becomes  y=   -2 (x-1)^2 +3

 Feb 21, 2018
edited by ElectricPavlov  Feb 21, 2018
edited by ElectricPavlov  Feb 21, 2018
 #1
avatar+18057 
+2
Best Answer

1. 9x^2-18x      +9y^2 + 36y      = -44    divide thru by 9

      x^2 - 2x        + y^2 +4          = -44/9    'complete the square' for x and y

    ( x-1)^2          + (y+2)^2         = -44/9  + 1 + 4

     (x-1)^2 + (y+2)^2   =   1/9      Now this is standard form for a circle (x-h)^2 + (y-k)^2 = r^2 

where center is h,k  and r = radius   

center =  1,-2    radius = 1/3

 

2. Let's set this up as vetex form for a parabola     h, k = vertex = 1,3  (from graph)

   so      a(x-1)^2  + 3 =y   is the equation for this parabola...now let's find 'a'

           a convineint point which must satisfy this equation (on the graph) is  0,1 ...substitute this

 

          a (0-1)^2 + 3 = 1

              a+3 = 1

               a= -2      so the equation becomes  y=   -2 (x-1)^2 +3

ElectricPavlov Feb 21, 2018
edited by ElectricPavlov  Feb 21, 2018
edited by ElectricPavlov  Feb 21, 2018

27 Online Users

avatar
avatar
avatar